Role of Leadership in Enhancing Employees Performance: A Case Of Board of Intermediate and Secondary Education, Peshawar - Ullah, Dr. Mahboob; Alam, Dr. Waqar; Khan, Dr. Yasir; Joseph, Victoria; Farooq, Dr Syed Umar; Noreen, Sidra (The journal of contemporary issues in business and government, 2022)
Employee performance is a metric for determining how effective a person's job is. Hence, optimal job performance is one of the primary goals of an organization. Leadership has the ability to achieve work performance and turn the vision of the organization into reality. Better employee performance in the organization result from good leadership. The goal of this cross-sectional study is to examine the role of leadership (authoritative and laissez- faire), in enhancing employees' performance at Board of Intermediate and Secondary Education, Peshawar Pakistan. For accomplishment of research objective, primary data were acquired from employees of the Board of Intermediate and Secondary Education, Peshawar Pakistan by a self-administered adopted questionnaire to examine the association. The outcomes indicated that authoritative leadership has a positive and significant impact on employee performance. In addition, the employee engagement, on the other hand, has also a significant and positive correlation with employee performance. To maintain successful human resource utilization and high levels of employee work involvement and performance, it is recommended that moderate independence and effective supervision should be implemented at the workplace. It is suggested that organizations increase their organizational participation and performance by hiring managers with high leadership skills.